Superselective embolisation in acute lower gastrointestinal haemorrhage: a single institution experience - Md Ralib @ Md Raghib, Ahmad Razali; Zakaria, Rozman; Mohamad, Zahiah; Muda, Ahmad Sobri (Universiti Sains Malaysia, 2009)
Background: Superselective embolisation has been recognised as integral in the management of lower gastrointestinal haemorrhage. It has also reduced the need for emergency surgery. The objective of this case series was to describe the lower gastrointestinal haemorrhage cases seen in our centre, its diagnosis and the role of superselective embolisation in patient management. Methods: All patients who underwent superselective embolisation from January 2008 until April 2009 in our centre were analysed. Data were collected from the hospital electronic medical records. Results: Four patients (three males) with a mean age of 81 years were analysed. Multidetector computerised tomography and digital subtraction angiography were positive in all patients. Superselective embolisation with platinum microcoils was performed in all patients (n = 4). Technical success was achieved in all patients (100%). Conclusion: Superselective embolisation in the treatment of lower gastrointestinal haemorrhage is safe and effective with a very high technical success rate.